Study of organoleptic and technological properties of fish maffins with addition of pearly powder - Kondratiuk, Natalia Vyacheslavivna; Stepanova, Tetiana Mykhailivna; Viyenko, Oleksiy Yuriyovich; Shen, Yunjian (НТУ "ХПІ", 2019)
The authors propose a new type of snack muffins with the addition of dry minced fish from sea and freshwater fish, enriched with pearl powder. It provides high protein content and good taste of finished products. The article presents the results of experimental studies on the enrichment of dry minced fish with pearl powder and the addition of these compositions to the recipes of snack muffins. Tasting analysis showed that the best organoleptic indicators have samples of flour culinary products with the content of enriched dry minced fish in 25%. However, such a quantity of recipe ingredients introduced negatively affects the process of dough formation and the appearance of finished products. The amount of added pearl powder was 2.3% of the amount of dry minced fish. The increase in the amount of added pearl powder to 5% does not contribute to an increase in the hydrophilic-city of dry minced fish in the composition of the dough piece for snack muffins. A further increase above 5% adversely affects the organoleptic characteristics of the finished culinary products. Thus, the accepted amount of dry minced fish was 15%. Adding 2.3% of pearl powder to the amount of dry minced fish allowed the physiological required ratio of calcium and phosphorus, which was 2:1 and provide preventive doses of organically bound calcium and phosphorus by 24-28% depending on age.

Автори пропонують новий вид закусочних мафінів із внесенням сухого рибного фаршу з морських і прісноводних риб, збагаченого перлинною пудрою, що забезпечують підвищений вміст білка і гарний смак готових виробів. У статті представлені результати експериментальних досліджень по збагаченню рибних сухих фаршів перлинним порошком і додаванню отриманих композицій до складу рецептурної суміші закусочних мафінів. Дегустаційний аналіз показав, що найкращими органолептичними показниками володіють зразки борошняних кулінарних виробів із вмістом збагаченого рибного сухого фаршу в 25%. Однак, така кількість внесених рецептурних інгредієнтів негативного впливає на процеси тістоутворення і зовнішній вигляд готових виробів. Кількість внесеної перлинної пудри склала 2,3% від кількості сухого рибного фаршу. Збільшення кількості введеної добавки перлинної пудри до 5% не сприяє збільшенню гідрофільності сухого рибного фаршу у складі тістової заготовки для закусочних мафінів. Подальше збільшення вище 5% негативно впливає на органолептичні показники готової кулінарної продукції. Таким чином, прийнята кількість внесеного рибного фаршу склала 15%. Внесення 2,3% перлинної пудри від кількості сухого рибного фаршу дозволило забезпечити фізіологічні необхідне співвідношення кальцію і фосфору, яке склало 2:1 і забезпечити профілактичні дози органічно зв'язаного кальцію і фосфору на 24-28% залежно від віку.
Дослідження органолептичних і технологічних властивостей рибних маффінів із додаванням перлинної пудри
Keywords: snack muffins; dry minced fish; pearl powder; calcium; phosphorus; закусочні мафіни; сухий рибний фарш; кальцій; фосфор